Report of a Confirmed SARS-CoV-2 Positive Newborn after Delivery Despite Negative SARS-CoV-2 Testing on Both Parents - Harding, Benjamin R.; Vora, Farha (American Journal of Perinatology Reports, 2021)
We present a case of a term infant born to an asymptomatic mother at a community hospital who required transfer to a local neonatal intensive care unit (NICU) immediately after birth for respiratory distress. The infant was tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at 24 hours of life by reverse transcription polymerase chain reaction (RT-PCR) testing due to the absence of prenatal maternal COVID-19 testing and was found to be positive for SARS-CoV-2 at that time. A second RT-PCR test was obtained on the infant on day of life (DOL) 4 and was also positive, confirming an accurate diagnosis of COVID-19 disease in the infant. Both the mother and father remained asymptomatic and concomitantly tested negative for SARS-CoV-2 on two separate occasions. The infant subsequently clinically improved and was discharged without any complications. This case raises the potential concern for two unreported newborn issues related to COVID-19. First, the potential unreliability of negative maternal COVID-19 testing surrounding the time of delivery as it relates to routine newborn testing and isolation needs, and second, if the negative material testing was accurate, this raises the concern for a potential case of nosocomial COVID-19 infection within the first 24 hours of life.
Keywords: SARS-CoV-2; COVID-19; newborn; asymptomatic; congenital; infection; nosocomial